The Milky Way as Seen by Classical Cepheids. I. Distances Based on Mid-infrared Photometry - Dorota M. Skowron; Ronald Drimmel; Shourya Khanna; Alessandro Spagna; Eloisa Poggio; Pau Ramos (The Astrophysical Journal Supplement Series)
Classical Cepheids are the archetype of the standard candle, thanks to the period–luminosity relation, which allows us to measure their intrinsic brightness. They are also relatively young and bright, potentially making them excellent tracers of the young stellar population that is responsible for shaping the visible aspect of our Galaxy. However, being observers embedded in the dusty interstellar medium of the Galaxy, deriving reliable photometric distances to classical Cepheids of the Milky Way is a challenge. The typical approach is to use “reddening-free” indices, such as Wesenheit magnitudes, to obviate the need for an extinction correction. However, this approach could lead to unknown systematics—especially toward the inner Galaxy—as its assumption of a universal total-to-selective extinction ratio is not satisfied, particularly in lines of sight where the extinction is high and crosses spiral arms. We instead estimate new distances for 3424 Cepheids based on mid-IR photometry from the Wide-field Infrared Survey Explorer, which suffers minimally from extinction, and by adopting a 3D extinction map to calculate the necessary (albeit small) extinction corrections. We show that our distances are consistent with Gaia’s parallaxes for the subset with relative parallax errors smaller than 10%, verifying that our mean distance errors are of the order of 6% and that the mean parallax zero-point for this subsample is 7 μ as.